The onset of transient convection in bottom heated porous media - Tan, Ka-Kheng; Sam, Torng; Jamaludin, Hishamuddin (Elsevier Science, 2003)
The theory of transient convection in bottom heated porous media under constant heat flux (CHF) condition or fixed surface temperature (FST) condition is advanced and verified by computational fluid dynamics (CFD) simulations. The use of κ*, instead of κ m tends to artificially inflate the value of Rayleigh number by about 30%. A new transient Rayleigh number for unsteady-state heat conduction was defined to predict the onset of transient convection in porous media, which were successfully simulated. The critical transient Rayleigh number from the simulation for CHF was about 29.60, which is close to the theoretical value of 27.1 calculated by Ribando and Torrance in 1976. In the case of FST, the critical transient Rac was found to be 30.9, which is close to the theoretical value of 32.3. The critical times of onset for simulations were predicted with good accuracy. The prediction of the critical wavelengths of the emerging plumes were fair for the 2D simulations. Any experiment to verify the linear stability analysis for thermal instability must simultaneously concur in the three eigenvalue parameters, namely the Biot number, the critical wavenumber and the corresponding critical Rayleigh number, apart from the physical boundaries. The average maximum transient Nusselt number was found to be 3.41 for CHF and 3.5 for FST respectively.